The Effect of Everolimus on Subependymal Giant Cell Astrocytoma (SEGA) in Children with Tuberous Sclerosis Complex - Bakhtiary, Hassan; Barzegar, Mohammad; Shiva, Shadi; Poorshiri, Bita; Hajalioghli, Parisa; Herizchi Ghadim, Hamideh (Iranian Journal of Child Neurology, 2021)
Objective: Subependymal Giant Cell Astrocytomas (SEGAs) are slow-growing glioneuronal tumors typically found around the ventricles of the brain, particularly near the foramen of Monro in 15%-20% of patients with tuberous sclerosis complex (TSC). Surgical resection is the standard treatment for these symptomatic tumors. The mTOR inhibitor everolimus can be regarded as an alternative treatment of SEGAs due to the complications of surgery. Materials & Methods: This pre- and post-treatment clinical trial was performed on 14 children (eight females and six males with a mean age of 10 years) previously diagnosed with TSC based on the diagnostic criteria. The subjects received oral everolimus at a dose of 3 mg/m2 for at least six months. The present study primarily aimed to specify the effect of this medication on SEGA volume change before and after treatment. Secondary objectives were to determine the effect of this drug on renal angiomyolipoma (AML), skin lesions, and seizures in TSC patients. Results: Half of the patients had more than 30% of volume loss in SEGA; in 28.5% of them the response rate of ≥ 50% reduction in SEGA volume was achieved (P=0.01). Moreover, 92.9% of the patients had ≥ 50% decrease in the frequency of seizures (P=0.000). The response rates in AML and skin lesion were 14.2% and 50%, respectively. Conclusion: Everolimus significantly reduced the seizure frequency and SEGA volume in the subjects, hence, a potential alternative treatment for symptomatic SEGA in TSC patients.